(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the effect of dentin contamination and cleaning techniques on the bond strength of resin-modified glass ionomer (RMGI)/dentin interfaces.168 bovine teeth were selected and divided into twelve groups (n = 14), according to the contaminating agent (S - no contamination; Sa - saliva; Sg - blood; H - hemostatic) and cleaning technique (S - without cleaning; A - air and water spray; P - polyacrylic acid reconditioning 26%). All specimens were restored with Riva Light Cure (SDI) ionomeric material, sectioned (1.0 × 1.0 mm toothpicks), and subjected to the microtensile bond strength test and a thermocycling regimen (CT). In the immediate analysis, all contaminated groups without cleaning had the following adhesion values when compared with the control group. After thermocycling, in the groups without cleaning only the hemostatic was identified to the control. The Sa groups maintained the immediate analysis standard, while the Sg groups were similar to the control, regardless of the time analyzed. Groups H were similar to each other. In conclusion, the contaminants tested impaired the immediate adhesion of the ionomeric material to dentin. Substrate reconditioning was effective in specimens contaminated with saliva and hemostatic agent. However, bond strength values reduced after aging.